2003
DOI: 10.1172/jci200317712
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory functions of vascular endothelial growth factor in alloimmunity

Abstract: Vascular endothelial growth factor (VEGF), an established angiogenesis factor, is expressed in allografts undergoing rejection, but its function in the rejection process has not been defined. Here, we initially determined that VEGF is functional in the trafficking of human T cells into skin allografts in vivo in the humanized SCID mouse. In vitro, we found that VEGF enhanced endothelial cell expression of the chemokines monocyte chemoattractant protein 1 and IL-8, and in combination with IFN-γ synergistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 47 publications
6
72
0
1
Order By: Relevance
“…VEGF has been shown to reduce apoptosis in a large number of cells and cell lines, many of which express VEGF-R1. These include cancer cells, e.g., breast, prostate, and multiple myeloma cells (1,22,27) as well as normal neurons (33), monocytes (36), skeletal myoblasts (18) in mammals, and hematopoietic cells in both mammals and Drosophila (6,16). The mechanisms through which VEGF reduces apoptosis, as shown here, and increases podocyte cell survival (14) are unknown.…”
Section: Discussionmentioning
confidence: 91%
“…VEGF has been shown to reduce apoptosis in a large number of cells and cell lines, many of which express VEGF-R1. These include cancer cells, e.g., breast, prostate, and multiple myeloma cells (1,22,27) as well as normal neurons (33), monocytes (36), skeletal myoblasts (18) in mammals, and hematopoietic cells in both mammals and Drosophila (6,16). The mechanisms through which VEGF reduces apoptosis, as shown here, and increases podocyte cell survival (14) are unknown.…”
Section: Discussionmentioning
confidence: 91%
“…A study by Detmar et al (42) reported that transgenic overexpression of VEGF 164 in the skin of mice led to large increases in leukocyte rolling and firm adhesion and that these mice showed increased vascular density composed of immature vessels, indicating a molecular link between leukocyte recruitment and angiogenesis. Recent reports also demonstrate that VEGF-A is a potent immune modulator under several conditions such as ischemiareperfusion and alloimmunity (126,156). VEGF-A stimulation of human umbilical vein endothelial cells increases the expression of adhesion molecules, such as ICAM-1, VCAM-1, and selectins (68,75).…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 99%
“…43 It is also interesting, in light of the success of anti-VEGF therapies in the management of neovascular AMD, that VEGF itself increases expression of endothelial cell adhesion molecules and elevates recruitment of macrophages and neutrophils under some conditions, in addition to its well-appreciated direct effects on vascular growth. 44,45 How might macrophages protect against macular degeneration?…”
Section: How Might Macrophages Promote Macular Degeneration?mentioning
confidence: 99%